Long-range planning : the executive viewpoint - Warren, E. Kirby (Englewood Cliffs, N.J. : Prentice-Hall, 1966)
The book presents a critical evaluation of the state of the art of long-range planning in business.
Includes index.
Includes bibliographical references: p. 92-101.
rpm 25/01/2019
Loans
Keywords: Industrial management